2020
DOI: 10.1101/2020.09.01.277467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experience-dependent structural plasticity in the adult brain: How the learning brain grows

Abstract: Volumetric magnetic resonance imaging studies have shown that intense learning can be associated with grey matter volume increases in the adult brain. The underlying mechanisms are poorly understood. Here we used monocular deprivation in rats to analyze the mechanisms underlying use-dependent grey matter increases. Optometry for quantification of visual acuity was combined with volumetric magnetic resonance imaging and microscopic techniques in longitudinal and cross-sectional studies. We found an increased sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In most cross‐sectional studies, healthy controls are not divided into young‐aged and middle‐aged subgroups because the adult brain is thought stable during adulthood. However, neuroplasticity could also cause obvious structural alterations in matured brain (Kwok et al, 2011; Schmidt et al, 2021; Ziegler et al, 2012), therefore, age‐specific structural changes in healthy controls should not be neglected. In current study, widespread structural changes were found between young‐aged and middle‐aged healthy controls (Figure S2), demonstrating a nonuniform structural pattern in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cross‐sectional studies, healthy controls are not divided into young‐aged and middle‐aged subgroups because the adult brain is thought stable during adulthood. However, neuroplasticity could also cause obvious structural alterations in matured brain (Kwok et al, 2011; Schmidt et al, 2021; Ziegler et al, 2012), therefore, age‐specific structural changes in healthy controls should not be neglected. In current study, widespread structural changes were found between young‐aged and middle‐aged healthy controls (Figure S2), demonstrating a nonuniform structural pattern in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In total 83 HIV subjects, 17 subjects had no history of taking drugs, and 3 subjects took medication less than 10 days, who were excluded for further analysis. Sixty‐three patients with HIV infection were finally enrolled, and underwent the cART consisting of tenofovir/lamivudine/efavirenz or tenofovir/lamivudine/lopinavir/ritonavir, which resulted in the same CNS penetration effectiveness score for each subject (Eggers et al, 2017; Schmidt et al, 2021). Table 2 listed the detailed information of subjects in each subgroup.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, plasticity in normally functioning brain is a prerequisite basis of learning and memory that involves plastic adaptation such as long-term potentiation (LTP). This is opposed to plastic changes observed using MRI in cerebral stroke pathology, that involves modification in intracortical myelin, augmented neurogenesis, improved spine density in neuronal dendrites and alterations in astrocyte volume [64].…”
Section: Concept Of Recovery After Post Stroke Cerebral Damagementioning
confidence: 72%
“…Rehabilitation is known to improve cognitive functions of patients [42]. Neuroplasticity, that is, the adaptive changes of structural and functional neural circuitry in terms of molecular, synaptic, and cellular changes, is commonly cited as a potential explanation for the cognitive and functional recovery [57,62]. Although axonal sprouting and functional rewiring post TBI is reported [7,40], the underlying mechanism of change in white matter structural connectivity over time at the network level is still unclear [76].…”
Section: Revisiting Structural Plasticity In Tbimentioning
confidence: 99%